1991
DOI: 10.1063/1.105361
|View full text |Cite
|
Sign up to set email alerts
|

Donor-acceptor pair formation in InP doped simultaneously with Si and Zn during metalorganic chemical vapor deposition

Abstract: Deposition of InP by metalorganic chemical vapor deposition, simultaneously doped with both a donor (Si) and an acceptor (Zn) species during the growth, has been carried out. The incorporation of Si is not affected by the presence of Zn, but the Zn incorporation is substantially enhanced by the presence of Si. These results are consistent with the formation of donor-acceptor pairs, which has been suggested earlier to explain Zn diffusion profiles in Si-doped InP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…For example, incorporation of both the deep-donor oxygen and the shallow-donor Te is enhanced in Mgdoped Al 0.5 In 0.5 P, while Mg has little or no effect on the incorporation of S and Si in Al 0.5 In 0.5 P. This observation regarding the effect of Mg on S or Si incorporation is consistent with previous reports in the literature, which indicate that both S and Si enhanced Zn incorporation in InP, but Zn did not enhance S or Si incorporation in InP. 10,13 The difference between the effect of Mg on the incorporation of these various donor species is not well understood.…”
Section: Comparison Of the Effect Of Oxygen Te S And Si On Mg Incosupporting
confidence: 94%
See 2 more Smart Citations
“…For example, incorporation of both the deep-donor oxygen and the shallow-donor Te is enhanced in Mgdoped Al 0.5 In 0.5 P, while Mg has little or no effect on the incorporation of S and Si in Al 0.5 In 0.5 P. This observation regarding the effect of Mg on S or Si incorporation is consistent with previous reports in the literature, which indicate that both S and Si enhanced Zn incorporation in InP, but Zn did not enhance S or Si incorporation in InP. 10,13 The difference between the effect of Mg on the incorporation of these various donor species is not well understood.…”
Section: Comparison Of the Effect Of Oxygen Te S And Si On Mg Incosupporting
confidence: 94%
“…[4][5][6][7][8][9][10][11][12][13] The observation of enhanced Mg incorporation in the presence of the deep-donor oxygen thus suggests that oxygen may also influence Mg diffusion in these samples. In fact, further inspection of the SIMS data in Fig.…”
Section: Mg-oxygen Dopant Interactions In A1 05 In 05 Pmentioning
confidence: 89%
See 1 more Smart Citation
“…32 The incorporation of Si is proportional to the disilane flow and the incorporation efficiency is high, i.e., the silane flow needed to achieve our target doping levels is an order of magnitude lower than the TMIn flow. 33 However, Zn doping normally has a very low incorporation efficiency, 34,35 so less than 0.2% of the molecules injected into the reactor were incorporated into the crystal matrix with a molar ratio TMIn/DeZn ≈ 50.…”
Section: Dopingmentioning
confidence: 99%
“…Diffusion 1,2 and in situ doping 3,4 are normally used for Zn doping. It was reported that the hole concentration in Zn-diffused InP was 0.5%-10% of the total Zn concentration.…”
Section: Introductionmentioning
confidence: 99%